1988
DOI: 10.1103/physrevc.38.1153
|View full text |Cite
|
Sign up to set email alerts
|

Elastic deuteron scattering and optical model parameters at energies up to 100 MeV

Abstract: Differential cross sections of elastic scattering of deuterons on the target nuclei 'Al, Y, ' Sn, and Pb were measured at Ed --58.7 MeV and Ed --85 MeV. "Best-fit" parameters in terms of the phenomenological optical model were extracted from the data including in addition differential cross section and analyzing power data from the literature. A set of global optical potential parameters is derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 43 publications
0
97
0
Order By: Relevance
“…With the gas target such a measurement is not possible as the scattered ions would have insufficient energy to pass through the gas volume and the windows. The elastic deuteron-scattering cross section was explored with four different optical-model calculations using different global parameterizations [34][35][36][37]. The calculated cross sections at the local maximum of θ lab = 11.4…”
Section: The Experimentsmentioning
confidence: 99%
“…With the gas target such a measurement is not possible as the scattered ions would have insufficient energy to pass through the gas volume and the windows. The elastic deuteron-scattering cross section was explored with four different optical-model calculations using different global parameterizations [34][35][36][37]. The calculated cross sections at the local maximum of θ lab = 11.4…”
Section: The Experimentsmentioning
confidence: 99%
“…The differences with respect to the evaluated total reaction cross sections of the ACSELAM library are about 25-30%. An additional comparison between the experimental data and the angular distributions calculated using the deuteron global OMP of Bojowald et al [12] showed the lack of reliability Fe isotopes between 5 and 56 MeV using the present phenomenological OMP (solid curves), the global potentials [11] (dash-dotted curves) and [12] (dotted curves), and the TALYS option based on Watanabe approach (dashed curves). 93 Nb isotopes between 12 and 52 MeV using the present phenomenological OMP (solid curves), the global potentials [11] (dash-dotted curves) and [12] (dotted curves), and the TALYS option based on Watanabe approach (dashed curves).…”
Section: Average Energy-dependent Phenomenological Ompmentioning
confidence: 99%
“…The deuteron elastic-scattering experiments on Al, Fe, Cu and Nb isotopes, at incident energies lower than 20 MeV, are not satisfactorily described by any of the phenomenological well-known OMPs of either Perey and Perey [9], Lohr and Haeberli [10], Daehnick et al [11], or Bojowald et al [12] as well as the recent analyses [13]. Moreover, the analysis of the low-energy elastic scattering data suffers from discrete and continuous ambiguities in the OMP parameters, whose uncertainties vary for various target nuclei and for different incident energies due to the precision of data analyzed.…”
Section: Semi-microscopic Analysis Of Deuteron Elastic Scatteringmentioning
confidence: 99%
See 2 more Smart Citations